DOMINATION SPECIES OF GASTROPODS IN THE LANAGA WATERS MEUREUBO DISTRICT WEST ACEH REGENCY ACEH PROVINCE - Asri Mursawal; Muhammad Ali Sarong; Muhammad Rizal; Ika Kusumawati; Rudi Hermi (Universitas Islam Negeri Ar-Raniry, 2022)
Gastropods are soft-bodied animals with stomachs as legs, live in land and waters, and have dominant nature in the area they inhabit, especially in the Lanaga Waters, Meureubo District, West Aceh Regency. This study aimed to (1) analyze the dominance level of each species of the Gastropod class inhabits the Lanaga Waters, and (2) determine the species of Gastropods dominates the Lanaga Waters, Meureubo District, West Aceh Regency, Aceh Province. The research was carried out from January to March 2021, in the Lanaga Waters, Meureubo District, West Aceh Regency, Aceh Province. The research area was divided into 9 stations based on the conditions of the aquatic environment, and each station was assigned to five sampling plots. Data were collected using purposive sampling technique, and data analysis was analyzed using the dominance formula and further described. The results showed that (1) the dominance index of each species of the Gastropod class ranged from 0.00001 to 0.710716, indicating a low to moderate level of dominance, and (2) the species from the Gastropod class dominated the Lanaga Waters, Meureubo District, Aceh Barat was Faunus ater, with a moderate level of dominance